Extracorporeal Membrane Oxygenation for Complex Multiorgan System Trauma - Michael S. Firstenberg; Karen Nelson; Erik Abel; John McGregor; Daniel Eiferman (Case Reports in Surgery)
With growing experience, the indications for salvage extracorporeal membrane oxygenation continue to expand. We describe a successful application of extracorporeal support in a polytrauma patient presenting with profound hypothermia, respiratory failure, and whom was later found to have an intracranial hemorrhage. We advocate the role of salvage therapy even in patients with complex pathophysiology despite perceived relative or absolute contraindications to extracorporeal support.